An alpaca nanobody inhibits hepatitis C virus entry and cell‐to‐cell transmission. Issue 3 (30th July 2013) - Tarr, Alexander W.; Lafaye, Pierre; Meredith, Luke; Damier‐Piolle, Laurence; Urbanowicz, Richard A.; Meola, Annalisa; Jestin, Jean‐Luc; Brown, Richard J. P.; McKeating, Jane A.; Rey, Felix A.; Ball, Jonathan K.; Krey, Thomas
<x xml:space="preserve">Abstract</x> Severe liver disease caused by chronic hepatitis C virus is the major indication for liver transplantation. Despite recent advances in antiviral therapy, drug toxicity and unwanted side effects render effective treatment in liver‐transplanted patients a challenging task. Virus‐specific therapeutic antibodies are generally safe and well‐tolerated, but their potential in preventing and treating hepatitis C virus (HCV) infection has not yet been realized due to a variety of issues, not least high production costs and virus variability. Heavy‐chain antibodies or nanobodies, produced by camelids, represent an exciting antiviral approach; they can target novel highly conserved epitopes that are inaccessible to normal antibodies, and they are also easy to manipulate and produce. We isolated four distinct nanobodies from a phage‐display library generated from an alpaca immunized with HCV E2 glycoprotein. One of them, nanobody D03, recognized a novel epitope overlapping with the epitopes of several broadly neutralizing human monoclonal antibodies. Its crystal structure revealed a long complementarity determining region (CD3) folding over part of the framework that, in conventional antibodies, forms the interface between heavy and light chain. D03 neutralized a panel of retroviral particles pseudotyped with HCV glycoproteins from six genotypes and authentic cell culture–derived particles by interfering with the E2‐CD81 interaction. In contrast to some of the most broadly neutralizing human anti‐E2 monoclonal antibodies, D03 efficiently inhibited HCV cell‐to‐cell transmission. Conclusion: This is the first description of a potent and broadly neutralizing HCV‐specific nanobody representing a significant advance that will lead to future development of novel entry inhibitors for the treatment and prevention of HCV infection and help our understanding of HCV cell‐to‐cell transmission. (Hepatology 2013;53:932–939)